2023
DOI: 10.3390/plants12152846
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trichoderma spp. on Fusarium oxysporum f. sp. asparagi and Fusarium wilt Control in Asparagus Crop

Abstract: Among the key diseases affecting the asparagus crop (Asparagus officinalis L.), vascular wilting of asparagus caused by Fusarium oxysporum f. sp. asparagi stands out worldwide. This disease significantly shortens the longevity of the crop and limits economic production. Traditional control measures have been largely ineffective, and chemical control methods are difficult to apply, making biological control approaches, specifically the use of Trichoderma, an economical, effective, and risk-free alternative. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Some rhizobacteria exhibit plant growth-promoting (PGPR) and biocontrol properties, making them promising candidates for managing plant diseases. Researchers identified different microorganisms such as Bacillus sp., 6,7 Pseudomonas sp., [8][9][10] Serratia sp., 8,11 and Trichoderma sp., [12][13][14][15] which would be potential candidates for management of plant diseases instead of chemical fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…Some rhizobacteria exhibit plant growth-promoting (PGPR) and biocontrol properties, making them promising candidates for managing plant diseases. Researchers identified different microorganisms such as Bacillus sp., 6,7 Pseudomonas sp., [8][9][10] Serratia sp., 8,11 and Trichoderma sp., [12][13][14][15] which would be potential candidates for management of plant diseases instead of chemical fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the biocontrol bacteria and fungi that have been shown to control plant root rot caused by Fusarium mainly include species of Bacillus [ 9 ], Penicillium [ 10 ], Pseudomonas [ 11 ], Streptomyces [ 12 ], and Trichoderma [ 13 ]. Among these, Bacillus has several beneficial characteristics, such as UV resistance, salt tolerance, and heat tolerance [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%